How to motivate salespeople to use CRM system efficiently through gamification elements : case Finnish media company - Petäsnoro, Rami (2017)
Consumers buying behavior has changed dramatically due to the development of digital sales. This has led companies to change their marketing strategy to become more cus-tomer-oriented. Nowadays companies are increasingly investing to different kind of in-formation system technologies. However, there are major shortcomings in the use of these systems. Many executives feel that systems are conducive to effective work and help in resource allocation. To achieve these goals, it is necessary to understand system requirements and the resources available to users. Specifically, salespeople’s motivation to use CRM system is crucial factor in system utilization. CRM system is collaborative tool, which enables efficient sales, and marketing processes if the system is used effi-ciently. Generally, this study investigates salespeople’s motivation to use CRM system. This research focuses on factors that increase and decrease salespeople’s motivation to use CRM system efficiently. As an advance this study examines gamification factors, which support salesperson's intrinsic or extrinsic motivation to use system. Through efficient use of the information systems companies are able to achieve competitive ad-vantage, which supports their own and customer’s value co-creation. Finally, this study considers how social influence and collaboration of other people affect to salesperson’s motivation. Main findings revealed that salespeople’s personal intention to use CRM system has remarkable impact on efficient system usage. These technologically oriented indi-viduals are the most likely to see faults in system utilization. The lack of proper training was noticed the most significant factor, which decreases salespeople’s motivation to use CRM system. This also causes a situation where users do not know what system can do and which features are included in the system. Second, salespeople felt that successful system usage demands also the supervisors to be committed. This will increase sales team motivation to utilize system when they are able to see comprehensive commitment towards system. Salespeople are competitive by nature. Therefore, CRM system must include elements, which support natural competition between salespeople. This study also suggests that system usage should not be based on external incentives but rather visible and measurable factors, which increase user’s intrinsic motivation.